MicroRNA Screening and the Quest for Biologically Relevant Targets. (September 2015) - Eulalio, Ana; Mano, Miguel
MicroRNAs (miRNAs) are a class of genome-encoded small RNAs that post-transcriptionally regulate gene expression by repressing target transcripts containing partially or fully complementary binding sites. Despite their relatively low number, miRNAs have been shown to directly regulate a large fraction of the transcriptome. In agreement with their pervasive role in the regulation of eukaryotic gene expression, miRNAs have been implicated in virtually all biological processes, including different pathologies. The use of screening technologies to systematically analyze miRNA function in cell-based assays offers a unique opportunity to gain new insights into complex biological and disease-relevant processes. Given the low complexity of the miRNome and the similarities to small interfering RNA (siRNA) screening experimental approaches, phenotypic screening using genome-wide libraries of miRNA mimics or inhibitors is not, per se, technically challenging. The identification of miRNA targets and, more importantly, the characterization of their mechanisms of action through the identification of the key targets underlying observed phenotypes remain the major challenges of this approach. This article provides an overview of cell-based screenings for miRNA function that were performed in different biological contexts. The advantages and limitations of computational and experimental approaches commonly used to identify miRNA targets are also discussed.